Vascular Microenvironment, Tumor Immunity and Immunotherapy - Lamplugh, Zachary; Fan, Yi (Frontiers in Immunology, 2021)
Immunotherapy holds great promise for treating cancer. Nonetheless, T cell-based immunotherapy of solid tumor has remained challenging, largely due to the lack of universal tumor-specific antigens and an immunosuppressive tumor microenvironment (TME) that inhibits lymphocyte infiltration and activation. Aberrant vascularity characterizes malignant solid tumors, which fuels the formation of an immune-hostile microenvironment and induces tumor resistance to immunotherapy, emerging as a crucial target for adjuvant treatment in cancer immunotherapy. In this review, we discuss the molecular and cellular basis of vascular microenvironment-mediated tumor evasion of immune responses and resistance to immunotherapy, with a focus on vessel abnormality, dysfunctional adhesion, immunosuppressive niche, and microenvironmental stress in tumor vasculature. We provide an overview of opportunities and challenges related to these mechanisms. We also propose genetic programming of tumor endothelial cells as an alternative approach to recondition the vascular microenvironment and to overcome tumor resistance to immunotherapy.